La poésie en question dans la première et la cinquième élégie de George Buchanan - Ferradou, Carine (Renaissance and Reformation / Renaissance et Réforme, 2013)
From the first verse of the first Elegy (entitled “Quam misera sit conditio docentium literas humaniores Lutetiae...”) written by Buchanan while he was a young teacher in Paris, the Scottish scholar depicts himself as an unlucky lover of poetry whose passion is impeded by his educational job. Through his fifth Elegy, “Ad Franciscum Oliuarius, Franciae Cancellarium, nomine Scholae Burdigalensis”, the Scottish scholar, then teaching Latin in Bordeaux, becomes the advocate of the Muses in order to obtain from the French Chancellor François Olivier the financial and moral help that classical studies need at the moment. In the first Elegy which testifies a personal experience as well as in the second one which is an “event poem” written for the defense of the Collège de Guyenne, Buchanan adopts the position of the poet complaining that too many difficulties prevent him from living completely and with dignity from his art whereas he embodies a sophisticated way of life, civilization in short. In both elegies, the status of the poet is seen as problematical: George Buchanan uses the topoi of the poet’s representation and of the current situation that is sometimes personal, sometimes shared by his fellow teachers in Bordeaux. Such a situation casts doubt on the poetical vocation of the “Prince of Poets of his time”, so called a little later by the French publisher Robert Estienne.